How to detect a small cluster in big data? - João, Paulo (2018)
João, P., & Lobo, V. (2014). How to detect a small cluster in big data? In Atas da 14ª Conferência da Associação Portuguesa de Sistemas de Informação: Os Sistemas de Informação na Saúde (Vol. 14, pp. 162-173). (Atas da Conferencia da Associacao Portuguesa de Sistemas de Informacao). Fundação Luis de Molina. DOI: 10.18803/capsi.v14.162-173